HUBUNGAN PERSEPSI REMAJA TENTANG PERNIKAHAN DINI DENGAN NIAT UNTUK MENIKAH DINI PADA REMAJA MASYARAKAT MADURA - Yessy Nur Endah Sary (JOMIS (Journal of Midwifery Science), 2025)
Adolescents, as the next generation approaches this stage of life, need to have a clear understanding of what it means to be marriage ready. Views and the possibility of changes in outlook on marriage and preparation impact the perception of early marriage. The researchers in this study set out to answer the question, "How do adolescents in Madurese feel about early marriage?" by looking at their attitudes and intentions towards the practice. A cross-sectional study is what this is. Simple random sampling is the method used for the sampling process. The number of participants in the study was 79. A survey on the attitudes and intentions of teenagers about early marriage and marriage at a young age served as the study tool. All respondents were required to sign an informed consent document before they could get the questionnaire. Chi square was the method of choice for analyzing the data.